Is a decrease of microparticles related to improvement of hemostasis after FVIII injection in hemophilia A patients treated on demand?. Issue 4 (11th April 2013) - Mobarrez, F.; Mikovic, D.; Antovic, A.; Antovic, J. P.
Summary Background Microparticles (MPs) are small membrane vesicles (0.1–1 μm) released from various cells after activation and/or apoptosis. There are limited data about their role in hemophilia A. Patients and Methods Blood samples were taken before and 30 min after FVIII injection in 18 patients with severe hemophilia A treated on demand. Flow‐cytometric determination of total MPs (TMPs) using lactadherin, platelet MPs (PMPs) (CD42a), endothelial MPs (EMPs) (CD144) and leukocyte MPs (LMPs) (CD45) was performed. The results were compared with data on endogenous thrombin potential (ETP), overall hemostatic potential (OHP), fibrin gel permeability and thrombin‐activatable fibrinolysis inhibitor (TAFI). Results and Conclusions TMPs and PMPs decreased after treatment (to 1015 ± 221 [SEM] and 602 ± 134 × 106 L−1) in comparison with values before treatment (2373 ± 618 and 1316 ± 331; P < 0.01). EMPs also decreased after treatment (78 ± 12 vs. 107 ± 13; P < 0.05) while LMPs were not influenced. Both TMP and PMP counts were inversely correlated, moderately but statistically significantly, with data on OHP, ETP, fibrin network permeability and TAFI/TAFIi (P < 0.05 for all). EMP counts were correlated only with ETP (P < 0.05), while LMP counts did not show any correlation. TMP and PMP counts were also inversely correlated with FVIII levels (P < 0.05). TMP, PMP and EMP counts decreased after on‐demand treatment with FVIII concentrate in hemophilia A patients. The decrease in circulating MPs, which were inversely correlated with hemostatic activation, may imply that MPs are incorporated in the hemostatic plug formed after FVIII substitution at the site of injury.